Fokalisasi Tiga Cerpen Pilihan dalam Kumpulan Cerpen Taman Tanpa Aturan Karya Noor. HD : Kajian Naratologi Gerard Genette - Aryulita, Erlin; Novi Siti Kussuji Indrastuti; Venny Indria Ekowati (Kawruh: Journal of Language Education, Literature and Local Culture, 2025)
A collection of short stories entitled Taman Tanpa Aturan by Noor H. Dee presents childern's imagination from the knowledge and symbols they encounter. The world of children filled with curiosity in Taman Tanpa Aturan is provided through high level of fantasy genre story. Three most interesting of twenty-four story titles in Taman Tanpa Aturan short story collection have been selected: 1) Rambut Jeruk Alma, 2) Gelembung Sabun, dan 3) Taman Tanpa Aturan. The three selected short stories raise questions about the influence of focalization (the narator's voice) on the delivery of the message. Using the narratology research by Gerard Genette, this research reveals the narrative technique used by Noor H. Dee in delivering messages to children through his work. The research data source from selected short stories in the short story collection Taman Tanpa Aturan. Using a qualitative descriptive method, the data in the from of words, phrases, and sentence in this study were analyzed using Gerard Genette's narrative technique consisting of duration, mood, and voice. The result of the data analysis in this study show that the message contained in the three short stories between the messages received by child readers and adult readers can have differences. The difference in message reception known through the narrative level which is in extradiegetic-heterodiegetic with zero focalization in the short story entiteld Rambut Jeruk Alma and Gelembung Sabun, and selective heterodiegetic in Taman Tanpa Aturan because the focalization is composed of a combination of zero and internal focalization.